Thermal and photochemical stability of poly(vinyl alcohol)/modified lignin blends - Fernandes, D. M.; Hechenleitner, AAW; Job, A. E.; Radovanocic, E.; Pineda, EAG (Elsevier B.V., 2006)
A kraft lignin derivative (KLD) obtained by reaction with p-aminobenzoic acid/phthalic anhydride was blended with poly(vinyl alcohol) (PVA) by solution casting from DMSO. PVA and PVA/KLD films were exposed to ultraviolet radiation (24, 48, and 96 h) and analyzed by thermogravimetry (TG), differential scanning calorimetry (DSC), infrared spectroscopy (FTIR), hydrogen nuclear magnetic resonance (H-1 NMR) spectroscopy, and scanning electron microscopy (SEM). PVA films show a loss of thermal stability due to irradiation. PVA/KLD reveals greater thermal stability than PVA and an increase in thermal stability after irradiation. These results suggest that the incorporation of KLD into PVA provides a gain in thermal and photochemical stability. FTIR, H-1 NMR, DSC, and TG results obtained for the blends suggest that intermolecular interactions between PVA and KLD chains are present. SEM micrographs revealed blend miscibility for a KLD blend content of up to 15 wt%, as observed at magnification of 1000 times. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: kraft lignin derivative; poly(vinyl alcohol); blends; NMR; FTIR; SEM